Self-Awareness Of Farmers In Snakebite Management In Panti District, Jember Regency: SELF-AWARENESS OF FARMERS IN SNAKEBITE MANAGEMENT IN PANTI DISTRICT, JEMBER REGENCY - Rismawan Yunanto; Wantiyah; Nigitha Novia Permatasari; Siswoyo; Baskoro Setioputro (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Background: Inappropriate preventive measures are one of the contributing factors, namely the lack of public awareness about prevention efforts, namely the use of protective equipment such as boots, lack of public understanding regarding the types of venomous snakes and the level of danger from snakes is also one of the factors causing snakebites. Aim: to find out the Self-Awareness of farmers in carrying out first aid management for snake bites. Study Design: Quantitative descriptive research design. The research design used is a survey research design. The sample in this study were 100 farmers in 4 villages, namely Panti Village, Suci Village, Serut Village, and Glagahwero Village, Panti District, Jember Regency. Respondent data was obtained through collection using a self-awareness questionnaire. Result: Most of the farmers were male with a mean age of 41,07 (SD = 11,43). Length of work farmers with a median length of work 12.00 (Min-Max 1-50), the majority of the last education is high school (38%). Respondents stated that some snakes in Jember are non-venomous snakes (71%). perform first aid by keeping the bitten part of the body from moving as many as 79 respondents (79%). using a strong bond at the top of the bite wound as many as 81 people (81%). giving drinks containing alcohol to relieve pain as many as 79 respondents (79%). The use of anti-pain drugs has a balanced result, as evidenced by as many as (50%) answering Yes and as many as (50%) answering No. Conclusion: The farmers in Panti have a good self-awareness due to snakebite management. This study has implications, namely that a farmer in performing first aid management on snake bites can be influenced by knowledge, attitudes, and actions. Keywords: Self-awareness, Snakebite, Snakebite management of farmers